Molecular Evidence of Raccoon Dog (Nyctereutes procyonoides) as a Natural Definitive Host for Several Sarcocystis Species - Petras Prakas; Tamara Kalashnikova; Naglis Gudiškis; Donatas Šneideris; Evelina Juozaitytė-Ngugu; Dalius Butkauskas (Pathogens)
Sarcocystis parasites infect a wide range of animals, including reptiles, birds, and mammals, and have complex two-host prey–predator life cycle. Sarcocysts are mainly found in the muscles of intermediate hosts, and oocysts sporulate in the intestines of the definitive host. The raccoon dog (Nyctereutes procyonoides), native to Asia and invasive in Europe, is a known disease carrier. However, studies on raccoon dogs in the transmission of Sarcocystis are scarce. Between 2019 and 2024, a total of 26 raccoon dog carcasses were collected in Lithuania. The results of a light microscopy examination indicated that 50% of the samples were positive for Sarcocystis spp. sporocysts and sporulated oocysts. Based on nested PCR and sequencing of cox1, 88.5% of the samples were positive for these parasites. Molecular analysis revealed the presence of 11 different Sarcocystis species. Eight species, including S. alces, S. capracanis, S. hjorti, S. iberica, S. linearis, S. morae, S. tenella, and S. venatoria were reported for the first time in raccoon dogs as definitive hosts. The identified Sarcocystis species were linked to intermediate hosts, such as cervids, wild boars, pigs, goats, and sheep. These findings suggest that raccoon dogs play a key role in the spread of Sarcocystis, particularly species infecting cervids.